UPAYA MENINGKATKAN HASIL BELAJAR DRIBBLE BOLA BASKET MELALUI PENGGUNAAN MEDIA AUDIOVISUAL - Frilyandi Kurniawan; Budi Budi; Elang Fauzan (Journal of Physical Education and Sport Science, 2020)
This research has a goal in developing children's learning through audiovisual media. This research method is a Classroom Action Research. The population in this study were class VIII students of SMP Negeri 7 Kuningan, semester II of the 2019/2020 school year. Determination of the sample using purposive sampling technique with 32 people to be the research subjects. Data collection techniques by doing (observation) and documentation. The results of the analysis of the output table "Paired Samples Test", the value of "Mean Paired Differences" is -19.063. This value shows the difference between the average learning outcomes of Cycle 1 and the average learning outcomes of cycle 2 or 69.06 - 88.13 = -19.063 and the difference is between -21.974 to -16.151 (95% Confidence Interval of the Difference Lower and Upper). It is known that the Sig. (2-tailed) value is 0.000 <0.05, then H0 is rejected and Ha is accepted. So it can be concluded that there is an average difference between the learning outcomes of cycle 1 and cycle 2, which means that there is an effect of using audiovisual media on dribble learning outcomes in basketball games in class VIII students of SMP Negeri 7 Kuningan.